2011
DOI: 10.1080/02699931.2010.551185
|View full text |Cite
|
Sign up to set email alerts
|

Defining reactivity: How several methodological decisions can affect conclusions about emotional reactivity in psychopathology

Abstract: There are many important methodological decisions that need to be made when examining emotional reactivity in psychopathology. In the present study, we examined the effects of two such decisions in an investigation of emotional reactivity in depression: (1) which (if any) comparison condition to employ; and (2) how to define change. Depressed (N = 69) and control (N = 37) participants viewed emotion-inducing film clips while subjective and facial responses were measured. Emotional reactivity was defined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…There are several different ways to calculate change between conditions (Nelson, Shankman, Olino, & Klein, 2011). For the correlational analyses, we elected to use residual scores rather than subtraction-based difference scores, which are less effective at isolating variance unique to a particular condition, primarily because the resulting difference score remains correlated with both initial values (Cronbach, & Furby, 1970; DuBois, 1957).…”
Section: Methodsmentioning
confidence: 99%
“…There are several different ways to calculate change between conditions (Nelson, Shankman, Olino, & Klein, 2011). For the correlational analyses, we elected to use residual scores rather than subtraction-based difference scores, which are less effective at isolating variance unique to a particular condition, primarily because the resulting difference score remains correlated with both initial values (Cronbach, & Furby, 1970; DuBois, 1957).…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of using multiple definitions of change is to ensure that our methods do not influence the results of this study and to ensure similar findings despite the analyses chosen. Previous research has suggested using several definitions of change to understand whether methodological decisions affect findings, especially when using data from randomized trials (Nelson, Shankman, Olino, & Klein, 2011; Twisk & Proper, 2004) Therefore, we used multiple versions of our outcome variable to evaluate the effects of the depression interventions as a whole. These included (1) posttest depression scores, (2) absolute change in depression, and (3) residualized change using unstandardized residuals.…”
Section: Methodsmentioning
confidence: 99%
“…First, we performed a linear regression analysis of the posttest IDS-C 30 score (as the outcome variable) on the baseline IDS-C 30 score (as the comparison measurement) (e.g., Nelson et al, 2011). Second, the unstandardized difference between the observed value at the posttest and the predicted value by the regression analysis in the first step was used as an outcome variable in our analyses to determine predictors of change in depression.…”
Section: Methodsmentioning
confidence: 99%
“…Studies examining group differences in the time course rather than just the immediate (or average) emotional ' The aforementioned studies also highlight the heterogeneity of anxiety disorders and that startle potentiation during viewing of aversive scenes is more associated with fear-related disorders (e.g., social phobia) than with distress-related disorders (e.g., depression/GAD; Watson, 2(X)5; Vaidyanathan et al, 2009). reaction are critical (Nelson, Shankman, Klein, & Olino, 2011). For example, group differences in the anticipation of and recovery from aversive stimuli may elucidate critical emotional regulatory processes in individuals with psychopathology (Larson, Nitschke, & Davidson, 2007;Nitschke et al, 2002).…”
Section: Present Studymentioning
confidence: 98%